Oregon geology - Orr, Elizabeth L. (Oregon State University Press, 2012)
A comprehensive treatment of the state’s geologic history, this book moves through Oregon’s regions to closely examine the unique geologic features of each, from the Blue Mountains to the Willamette Valley, from the High Lava Plains to the Coast Range.